Synchronous triple primary malignant tumours in the bladder, prostate, and lung harbouring TP53 and MEK1 mutations accompanied with severe cardiovascular diseases: A case report - Li Zhi-Ke; Zhao Qiang; Li Ning-Fu; Wen Jing; Tan Bang-Xian; Ma Dai-Yuan; Du Guo-Bo (Open Medicine, 2022)
Although the incidence of multiple primary malignancies (MPMs) is increasing, synchronous triple primary malignant tumours with prostate, bladder and lung is rarely reported. Gene mutation is thought to be a reason for MPMs, and severe cardiovascular diseases may interrupt the cancer treatment. Here we reported a 64-year-old male patient with synchronous triple primary malignant tumours of the bladder urothelial carcinoma, prostate adenocarcinoma, and non-small cell lung cancer (NSCLC) with mutations in TP53 and MEK1, all the three malignancies were diagnosed within 10 days. Although being interrupted by severe cardiovascular diseases (including myocardial infarction, venous thrombosis, and aneurism of the aortic root), he was successfully treated with radical cystoprostatectomy, chemotherapy plus pembrolizumab (a PD-1 antibody), and radiotherapy of the lung lesion, followed by maintenance monotherapy of pembrolizumab, overall survival was more than 26 months. In conclusion, a patient of synchronous triple primary malignant tumours with prostate, bladder, and lung harbouring TP53 and MEK1 mutations accompanied with severe cardiovascular diseases was treated successfully, which may suggest that comprehensive treatment, especially radical treatment such as operation and radiation, is very important for MPMs.